Clinical features of the pulmonary tuberculosis course combined with different diabetes mellitus types in the Zaporizhzhia region - Raznatovska, O. M.; Bobrovnycha-Dvizova, Yu. M.; Разнатовська, Олена Миколаївна; Бобровнича-Двізова, Ю. М.; Разнатовская, Е. Н.; Бобровничая-Двизова, Ю. М. (Запорожский государственный медицинский университет, 2017)
The purpose of the work – to determine the clinical features of the pulmonary tuberculosis course combined with different types of diabetes mellitus (DM) in the Zaporizhzhia region for the further development of the differentiated approach to the management of these patients. Materials and methods of research. The study included 49 patients with pulmonary tuberculosis who were in inpatient treatment in the Departments of Clinical site of the tuberculosis and pulmonology department of the ZSMU in the “Zaporizhzhia Regional Clinical TB Dispensary” Municipal institution. The patients were divided into 2 groups: a group of 1 – 31 patients with pulmonary tuberculosis combined with the 1 type DM course, a group of 2 to 18 patients with pulmonary tuberculosis combined with the 2 type DM course. The outcomes of the study were processed by modern analysis methods on a personal computer using the statistical package of the Statistica® for Windows 6.0 (StatSoft Inc., No. AXXR712 D833214FAN5) license program. Results. In tuberculosis patients with the combined type 1 DM course, regardless of sex, young people aged 31–40 years significantly predominate, and with type 2 diabetes – men over 40 years of age. In tuberculosis patients with the combined type 1 DM course, the infiltrative form of tuberculosis is 1.5 times more frequent than that of type 2 DM. In the case of the combined type 1 DM course, the tendency towards the infiltrative form predominance is determined, but compared to type 1 diabetes, the disseminated form is 10.4 times predominant. The vast number of patients in both groups are patients with bacterial excretion, and on discharge from hospital, the number of patients with bacterial excretion with the combined type 2 DM course remains 1.7 times larger. Regardless of the concomitant DM type, the vast majority of patients have a destructive process in the lungs with a predominance of cavities up to 4 cm in diameter, regardless of their number. Despite the fact that regardless of the concomitant DM type, the average time of the destructions healing in both groups is almost equal (5 months), in patients with type 2 DM there is a tendency to 2 times more frequent healing of destructions. Type 1 DM is of the predominantly severe and moderate severity in the subcompensation stage, and type 2 diabetes in almost all patients is of moderate severity with a tendency to the predominance of the decompensation stage. Regardless of the concomitant DM type, in the half of patients in the setting of the TB course combined with DM, the concomitant conditions are diagnosed: hypertonic disease and pulmonary heart failure in patients with the combined type 2 diabetes are prevalent in comparison with the patients with type 1 DM, where there is a tendency to increase in the pulmonary heart failure and hepatitis incidence. In TB patients, the complications of DM develop 1.3 times more frequent with type 1 than with type 2, which are manifested predominantly by diabetic vascular disorders, namely, retinal angiopathy and lower extremity angiopathy and ketoacidosis. And complications of type 2 diabetes are diabetic: vascular disorders, encephalopathy and diabetic foot. Regardless of the concomitant diabetes type, the incidence of adverse reactions to antimycobacterial drugs in cases of resistant tuberculosis is 37.5 % in patients with the combined type 1 DM and 44.4 % with the combined type 2 DM. In cases of tuberculosis with the combined type 2 DM, 5 times more patients have been provided with the palliative therapy. Conclusions. The course of tuberculosis largely depends on the type of diabetes. When combined with type 1 diabetes, the more unfavorable and severe course of both diseases is determined, while in combination with type 2 diabetes, on the contrary. Мета роботи – визначити клінічні особливості поєднаного перебігу туберкульозу легень із різними типами цукрового діабету (ЦД) у Запорізькій області для дальшої розробки диференційованого підходу до ведення цих пацієнтів. Матеріали та методи. У дослідження включили 49 хворих на туберкульоз легень, які перебували на стаціонарному лікуванні у відділеннях клінічної бази кафедри фтизіатрії і пульмонології ЗДМУ в КУ «Запорізький обласний протитуберкульозний клінічний диспансер». Хворі були поділені на 2 групи: 1 – 31 хворий на туберкульоз легень із поєднаним перебігом ЦД 1 типу, група 2 – 18 хворих на туберкульоз легень із поєднаним перебігом ЦД 2 типу. Результати дослідження опрацьовані сучасними методами аналізу на персональному комп’ютері з використанням статистичного пакета ліцензійної програми Statistica® for Windows 6.0 (StatSoft Inc., № AXXR712 D833214FAN5). Результати. У хворих на туберкульоз із поєднаним перебігом ЦД 1 типу, незалежно від статі, вірогідно переважають молоді особи віком 31–40 років, а з ЦД 2 типу – чоловіки (старші за 40 років). У хворих на туберкульоз із поєднаним перебігом ЦД 1 типу у 1,5 раза частіше переважає інфільтративна форма туберкульозу, ніж із ЦД 2 типу. А при поєднаному перебігу з ЦД 1 типу визначається тенденція до переважання інфільтративної форми, але порівняно з ЦД 1 типу у 10,4 раза переважає дисемінована. Переважна кількість пацієнтів обох груп – бактеріовиділювачі, а під час виписки зі стаціонара кількість пацієнтів із бактеріовиділенням при поєднаному перебігу з ЦД 2 типу залишається більшою в 1,7 раза. Незалежно від типу супутнього ЦД, основна кількість пацієнтів мають деструктивний процес із переважанням каверн до 4 см діаметром, незалежно від їхньої кількості. Притім, що, незалежно від типу супутнього ЦД, середні терміни загоєння деструкцій в обох групах майже однакові (5 місяців), при ЦД 2 типу визначається тенденція до частішого вдвічі загоєння деструкцій. ЦД 1 типу – переважно тяжкого та середньотяжкого ступенів тяжкості у стадії субкомпенсації, а ЦД 2 типу майже в усіх пацієнтів – середньотяжкого ступеня з тенденцією до переважання стадії декомпенсації. Незалежно від типу супутнього ЦД, у половини пацієнтів на тлі поєднаного перебігу туберкульозу з ЦД діагностуються супутні захворювання: у хворих із поєднаним ЦД 2 типу переважають гіпертонічна хвороба та легенево-серцева недостатність порівняно з хворими на ЦД 1 типу, де визначається тенденція до зростання частоти легенево-серцевої недостатності та гепатитів. У хворих на туберкульоз ускладнення ЦД розвиваються частіше у 1,3 раза при 1 типі, ніж при 2, проявляються переважно діабетичними судинними розладами, як-от: ангіопатіями сітківки ока та нижніх кінцівок і кетоацидозом. А ускладненнями ЦД 2 типу є діабетичні: судинні розлади, енцефалопатія та діабетична стопа. Незалежно від типу супутнього ЦД, частота побічних реакцій на антимікобактеріальні препарати у випадках резистентного туберкульозу становить 37,5 % у хворих із поєднаним ЦД 1 типу та 44,4 % – з поєднаним ЦД 2 типу. При туберкульозі з поєднаним ЦД 2 типу у 5 разів частіше пацієнти переведені на паліативне лікування. Висновки. Перебіг туберкульозу значно залежить від типу супутнього цукрового діабету. При поєднанні з цукровим діабетом 1 типу визначається несприятливіший і тяжкий перебіг обох захворювань, а при поєднанні з цукровим діабетом 2 типу – навпаки. Цель работы – определение клинических особенностей сочетанного течения туберкулеза легких с различными типами сахарного диабета (СД) в Запорожской области для дальнейшей разработки дифференцированного подхода к ведению этих пациентов. Материалы и методы. В исследовании приняли участие 49 пациентов с туберкулезом легких, которые прошли стационарное лечение в отделениях клинической базы кафедры фтизиатрии и пульмонологии ЗГМУ в КУ «Запорожский областной туберкулезный клинический диспансер». Пациенты разделены на 2 группы: группа 1 – 31 больной туберкулезом легких с сочетанным течением СД 1 типа, группа 2 – 18 больных туберкулезом легких с сочетанным течением СД 2 типа. Результаты исследования обработаны современными методами анализа на персональном компьютере с использованием статистического пакета лицензионной программы STATISTICA® для Windows 6.0 (Stat Soft Inc., AXXR712 D833214FAN5). Результаты. У больных туберкулезом с сочетанным течением СД 1 типа, независимо от пола, достоверно преобладают молодые люди в возрасте 31–40 лет, а с СД 2 типа – мужчины старше 40 лет. У больных туберкулезом с сочетанным течением СД 1 типа в 1,5 раза чаще преобладает инфильтративная форма туберкулеза, чем при СД 2 типа. А при сочетанном течении с СД 1 типа определяется тенденция к преобладанию инфильтративной формы, но по сравнению с СД 1 типа в 10,4 раза превышает диссеминированная. Подавляющее количество пациентов обеих групп являются бактериовыделителями, а при выписке из стационара количество пациентов с бактериовыделением при сочетанном течении с СД 2 типа остается больше в 1,7 раза. Независимо от типа сопутствующего СД подавляющее количество пациентов имеют деструктивный процесс в связи с преобладанием каверн до 4 см в диаметре, независимо от их количества. Притом, независимо от типа сопутствующего СД, средние сроки заживления деструкции в обеих группах почти одинаковые (5 месяцев), при СД 2 типа определяется тенденция к более частому в 2 раза заживлению деструкций. СД 1 типа преимущественно тяжелой и среднетяжелой степени тяжести – в стадии субкомпенсации, а СД 2 типа почти у всех пациентов – среднетяжелой степени с тенденцией к преобладанию стадии декомпенсации. Независимо от типа сопутствующего СД, у половины пациентов на фоне сочетанного течения туберкулеза с СД диагностируются сопутствующие заболевания: с сочетанным течением СД 2 типа преобладают гипертоническая болезнь и легочно-сердечная недостаточность по сравнению с больными с СД 1 типа, где определяется тенденция к росту частоты легочно-сердечной недостаточности и гепатитов. У больных туберкулезом осложнения СД развиваются чаще в 1,3 раза при 1 типе, чем при 2 типе, проявляются преимущественно диабетическими сосудистыми расстройствами, а именно: ангиопатиями сетчатки глаза и нижних конечностей и кетоацидозом. Осложнениями СД 2 типа являются диабетические сосудистые расстройства и энцефалопатия, диабетическая стопа. Независимо от типа сопутствующего СД, частота побочных реакций на антимикобактериальные препараты в случаях резистентного туберкулеза составляет 37,5 % у больных с СД 1 типа и 44,4 % – СД 2 типа. При туберкулезе с сочетанным течением СД 2 типа на паллиативное лечение переведено в 5 раз больше пациентов. Выводы. Течение туберкулеза значительно зависит от типа сопутствующего сахарного диабета. При сочетании с сахарным диабетом 1 типа определяется более неблагоприятное и тяжелое течение обоих заболеваний, а при сочетании с сахарным диабетом 2 типа – наоборот.
Клінічні особливості поєднаного перебігу туберкульозу легень із різними типами цукрового діабету
Клинические особенности сочетанного течения туберкулеза легких с различными типами сахарного диабета
Keywords: tuberculosis; diabetes mellitus; туберкульоз; цукровий діабет; туберкулез; сахарный диабет